2012
DOI: 10.1186/1477-9560-10-19
|View full text |Cite
|
Sign up to set email alerts
|

Platelet function in the postprandial period

Abstract: BackgroundPostprandial hyperlipidemia and hyperglycemia have been related to cardiovascular events. Among different underlying mechanisms platelet activation seems to be responsible too. No comparable data between various tests in normo- vs. hyperlipidemics before and at different time intervals are available after a fat meal. We aimed to compare 9 of them within the same patients at several time points in postprandial hyperlipidemia.ResultsFor some tests baseline values between the groups were significantly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Therefore, it could be that either there may be less platelets in the postprandial state or the clotting process, in which BDNF is released from platelets, is less efficient in the samples collected during the postprandial state. In this context, it was found that a high-fat meal elevated platelet count ( Sinzinger and Berent, 2012 ), but a high-carbohydrate meal did not ( Ahuja et al, 2009 ). Regarding the clotting process, it has been shown that meals rich in fats seem to activate coagulation factor VII which stimulates the clotting process ( Silveira, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it could be that either there may be less platelets in the postprandial state or the clotting process, in which BDNF is released from platelets, is less efficient in the samples collected during the postprandial state. In this context, it was found that a high-fat meal elevated platelet count ( Sinzinger and Berent, 2012 ), but a high-carbohydrate meal did not ( Ahuja et al, 2009 ). Regarding the clotting process, it has been shown that meals rich in fats seem to activate coagulation factor VII which stimulates the clotting process ( Silveira, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gel- filtered platelets (2.5 × 10 8 /mL) and PPP were prepared respectively. To minimize interference in the light transmission of PRP, which is commonly caused by postprandial chylomicrons and other lipid particles 69 , 125 µL gel-filtered platelets were incubated with its PPP (125 µL) for 20 min under 37 °C. The same volume of PPP and PIPES buffer were used as blank control.…”
Section: Methodsmentioning
confidence: 99%
“…Prior investigations examining the platelet activity in the postprandial state show conflicting evidence [ 15 , 16 , 20 , 36 , 37 ]. The reason for these discrepancies includes differences in methodology, different types of meals with different fat concentrations, as well as different measuring methods or various concentrations of agonists used in the tests, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, no exact sample size calculation could be performed on the given co-primary outcome variables. Alternatively, sample size estimation was performed according to the results on ADP-response of platelet-rich plasma after OFTT in patients with metabolic syndrome by Sinzinger et al [ 15 ]. Accordingly, 21 patients would be needed to show a significant difference in platelet activation (given a desired power of 0.8 and a p-value of 0.05) per group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation